An AC active power regulation method for MMC by employing the internal energy. (November 2022) - Lu, Xiaojun; Wang, Qi; Yang, Zhangbin; Zhang, Sixiang; Luo, Daijun; Li, Mengbo; Chen, Gong
Abstract: Similar to the onshore wind power integrated through AC transmission, the offshore wind power integrated through the modular multilevel converter (MMC) based HVDC also lays remarkable impacts on the stability of the power system. According to grid codes, offshore wind power should be capable of adjusting its active power fast. This paper proposes a fast regulation method at the onshore point of common coupling for offshore wind power by utilizing the energy stored in the distributed capacitors in the MMC. By carefully designing the curve of capacitor energy, the active power can vary expectedly. Meanwhile, no disturbance is placed on the DC-side active power or DC voltage. The effectiveness of the proposed method is verified by electromagnetic simulation.